Modeling healthcare demands and long-term costs following pediatric traumatic brain injury - Jared G. Wiegand; Zorays Moazzam; Bruno P. Braga; Bruno P. Braga; Sarah E. Messiah; Sarah E. Messiah; Sarah E. Messiah; Faisal G. Qureshi; Faisal G. Qureshi (Frontiers in Neurology)
IntroductionTraumatic brain injury (TBI) is a leading cause of death and disability in children, but data on the longitudinal healthcare and financial needs of pediatric patients is limited in scope and duration. We sought to describe and predict these metrics following acute inpatient treatment for TBI.MethodsChildren surviving their initial inpatient treatment for TBI were identified from Optum’s deidentified Clinformatics® Data Mart Database (2007-2018). Treatment cost, healthcare utilization, and future inpatient readmission were stratified by follow-up intervals, type of claim, and injury severity. Both TBI-related and non-TBI related future cost and healthcare utilization were explored using linear mixed models. Acute inpatient healthcare utilization metrics were analyzed and used to predict future treatment cost and healthcare demands using linear regression models.ResultsAmong 7,400 patients, the majority suffered a mild TBI (50.2%). For patients with at least one-year follow-up (67.7%), patients accrued an average of 28.7 claims and $27,199 in costs, with 693 (13.8%) readmitted for TBI or non-TBI related causes. Severe TBI patients had a greater likelihood of readmission. Initial hospitalization length of stay and discharge disposition other than home were significant positive predictors of healthcare and financial utilization at one-and five-years follow-up. Linear mixed models demonstrated that pediatric TBI patients would accrue 21.1 claims and $25,203 in cost in the first year, and 9.4 claims and $4,147 in costs every additional year, with no significant differences based on initial injury severity.DiscussionPediatric TBI patients require long-term healthcare and financial resources regardless of injury severity. Our cumulative findings provide essential information to clinicians, caretakers, researchers, advocates, and policymakers to better shape standards, expectations, and management of care following TBI.